The NANOSPONGES: AN INNOVATIVE DRUG DELIVERY SYSTEM: NANOSPONGES: AN INNOVATIVE DRUG DELIVERY SYSTEM - SIMRANJOT KAUR; SANDEEP KUMAR (Asian Journal of Pharmaceutical and Clinical Research, 2019)
For prolonged time there is a delusion for efficacious targeted drug delivery system, but the chemistry hold complex form had made situations thorny, but the development of new colloidal carrier called nanosponges (NSs) likely circumvent these problems. NSs are the nanoporous particles that can entangle a huge range of material and then be engulfed into a suitable formulation depend on the route of administration. They prevent the drug-protein degradation, lengthen the drug release in a controlled manner, and release the medicament to the target site. They can travel around the body and attach on the surface and liberate the drug in a controlled and predictable manner at the specific target site. They are fine aqueous solubility which makes them a bearer for low water-soluble drugs. Drugs having low bioavailability are best suited for this type of carrier system. Both lipophilic and hydrophilic drugs can be included in NSs. Particle size can change from smaller to bigger by varying the amount of crosslinker to the polymer. Various applications of NSs such as recovering bioavailability of active ingredient molecule and delivery of active ingredient into oral, topical, parenteral, and nasal route make them a superior candidate for targeted delivery of drugs. It can be used as a shipper for biocatalysts in the transport and release of enzymes, proteins, vaccines, and antibodies. They can be prepared by different methods such as emulsion solvent diffusion method, melt method, ultrasound-assisted method, Quasi emulsion solvent diffusion method. This analysis is focusing on the advantages, formulation, evaluation, application, and patent report of the NSs.